HEALTH CARE OF THE STAVROPOL TERRITORY ON THE EVE OF THE GREAT PATRIOTIC WAR - Yuliya Koshman (Гуманитарные и юридические исследования)
The article examines the development of public health services on the eve of the war in the Stavropol Territory. In the prewar period, medical workers and authorities had to face certain difficulties in organizing the health care system. The article also analyzes the outcomes on the eve of the Great Patriotic War, what exactly was done by the party and public organizations to build a clear structure in the health care system. How the issues of sanitary and epidemiological prosperity in the province were solved, what difficulties the medical workers had to face. In addition to issues related to the improvement of the sanitary and epidemiological situation in the province, medical workers took part in the development and testing of new methods to treat wounded and sick warriors of the participants in the Soviet-Finnish war, which were subsequently used in the Great Patriotic War. In addition, the pre-war period was a period of active construction of the resort network of the province, which was provided with the latest equipment and tools. Combined with natural factors and competent specialists it allowed the deployment of the largest hospital base in the country during the Great Patriotic War in the Caucasian Mineral Waters.